Lewis Acid Catalyzed Three-Component [3+2] Cycloaddition Reaction Using Pentafulvene as 2π Component: An Easy Way to Construct Pentaleno(1,2-b)indoles - Santhini, P. V.; Sarath Chand, S.; John, Jubi; Varma, R. Luxmi; Jaroschik, Florian; Radhakrishnan, K. V. (Synlett, 2017)
A facile route toward the synthesis of pentaleno(1,2-b)indoles via multicomponent reaction of indole, aldehyde, and pentafulvene is realized. The reaction proceeds through Lewis acid catalyzed [3+2] cycloaddition of in situ generated indolylmethanol and pentafulvene. This methodology provides an easy access to biologically relevant indole derivatives.
Keywords: fulvene; indole; cycloaddition; multicomponent reaction; cyclopentaleno indoles